Coupling reactions between reduced intermediates of insensitive munitions compound analog 4-nitroanisole. (May 2019) - Kadoya, Warren M.; Sierra-Alvarez, Reyes; Jagadish, Bhumasamudram; Wong, Stanley; Abrell, Leif; Mash, Eugene A.; Field, Jim A.
Abstract: Explosives, pesticides, and pharmaceuticals contain toxic nitroaromatic compounds that may form even more toxic azo compounds if they encounter reducing conditions in the environment. We investigated the mechanism by which 4, 4′-dimethoxyazobenzene forms in anaerobic sludge incubations of 4-nitroanisole, an analog for the insensitive munitions compound 2, 4-dinitroanisole (DNAN). Because studies have reported the mechanism to involve the coupling of reduced nitroaromatic intermediates, specifically aromatic amines and nitrosoaromatics, by nucleophilic processes, we abiotically paired 10 mM 4-aminoanisole with 2 mM 4-nitrosoanisole in nitrogen-flushed microcosms. However, only 7 μM of 4, 4′-dimethoxyazobenzene had formed after 24 h. We identified the major product to be 4-methoxy-4′-nitrosodiphenylamine. Repeating this experiment in phosphate buffer at pH 5.1, 7.1, and 8.6 demonstrated that the formation of this unexpected product is acid catalyzed. We found that 4-methoxy-4′-nitrosodiphenylamine is more toxic than 4, 4′-dimethoxyazobenzene to the bioluminescent bacterium Aliivibrio fischeri, with IC50 values of 0.1 μM and 0.5 μM, respectively. Both products are several orders of magnitude more toxic than reduced 4-nitroanisole intermediates 4-aminoanisole and 4-nitrosoanisole, as well as DNAN and its aromatic amine metabolites. Six-fold more 4, 4′-dimethoxyazobenzene formed when we incubated 4-nitrosoanisole with ascorbic acid, a reducing agent, than when we incubated 4-nitrosoanisole with 4-aminoanisole in the absence of ascorbic acid. We therefore suspect that 4-hydroxylaminoanisole, the first reduction product of 4-nitrosoanisole, is a better nucleophile than 4-aminoanisole and couples more readily with 4-nitrosoanisole. Slightly basic and reducing conditions can prevent the formation and persistence of toxic coupling products on sites contaminated with nitroaromatics, i.e. DNAN-contaminated firing ranges. Graphical abstract: Image 1 Highlights: Aminoanisole and nitrosoanisole abiotically couple to form a nitrosodiphenylamine. 4, 4′-dimethoxyazobenzene is a minor product of the reaction. Acidic pH values increased nitrosodiphenylamine formation. Nitrosodiphenylamine is more toxic than 4, 4′-dimethoxyazobenzene to A. fischeri . Hydroxylaminoanisole may couple more readily than aminoanisole with nitrosoansiole